(untitled) (National Administration Journal, 2025)
Digital marketing faces challenges driven by a rapidly changing demand that it had never experienced in its fully developed reality. Resilience, defined as the ability to experience the discomfort of difficulty and remain with it while continuing to live in the best possible way, emerges as an essential capacity to deal with the volatility, uncertainty, complexity, and ambiguity that characterize this sector. In this way, organizations can adapt to crises and turn challenges into opportunities. This article explores how continuous innovation, effective risk management, and social responsibility form the three pillars that can transform any company’s marketing strategy into a resilient marketing strategy. The paper examines cases and trends that have a significant impact on the business community, based on research from key articles and databases.